Adaptasi Pustakawan dalam Menghadapi Kemajuan Teknologi Informasi di Perpustakaan Utsman bin Affan Universitas Muslim Indonesia - Nasrullah, Nasrullah; Tawakkal, Tawakkal; Hasibuan, Nuriah (Jurnal El-Pustaka, 2022)
The purpose of this study was to determine the adaptations made by librarians in dealing with advances in information technology at the Uthman Bin Affan library at the Muslim University of Indonesia and the obstacles faced by librarians in dealing with advances in information technology at the Uthman Bin Affan library at the Indonesian Muslim University. This study uses a descriptive type of research with a qualitative approach. Data collection techniques used are through observation, interviews, and documentation. Sources of data used are primary data and secondary data. Data processing and analysis techniques are data reduction, data presentation, and verification. The results showed that the activities followed by librarians in adapting to advances in information technology at the Uthman Bin Affan library at the Muslim University of Indonesia were participating in seminars, workshops, conferences, and technical guidance related to the adaptation of librarians in the face of advances in information technology. The obstacles faced by librarians in dealing with advances in information technology are the lack of librarian initiative to participate in activities that support the adaptation of librarians in the face of advances in information technology, inadequate facilities such as internet networks, and the rapid development of information technology, making librarians overwhelmed in adapting to advances in information technology in the world. library.